Kilogram‐Scale Fabricated Organic Long‐Persistent Luminescence Materials with Multi‐Level Temperature Response. Issue 23 (7th September 2022) - Liu, Man; Zong, Jun; Wang, Lichang; Liu, Dongzhi; Wang, Tianyang; Hu, Wenping
Abstract: Purely organic long‐persistent luminescence materials (OLPLMs) have shown great application potential in the fields of anti‐counterfeiting and information encryption, due to their eco‐friendly preparation, low synthesis cost, and easy‐to‐tune luminescence. Notably, the development of efficient large‐scale fabrication methods will facilitate the commercial application of OLPLMs. Here, we realized the kilogram‐scale preparation of organic doped‐crystals with different long‐persistent luminescence durations by a facile water‐based method under ambient conditions. Additionally, the function of reversible multi‐level temperature response of LPL performance based on this kind of OLPLMs has been achieved, showing the unique application prospects in the field of anti‐counterfeiting and information encryption. This work provides an effective strategy for large‐scale fabrication of OLPLMs, and will accelerate the research and development of temperature‐responsive OLPLMs. Abstract : Kilogram‐scale organic doped‐crystals with different long‐persistent luminescence durations are fabricated by a facile water‐based method under ambient conditions. Based on these materials, the afterglow function of reversible multi‐level temperature response has been realized, showing unique application prospects in the field of anti‐counterfeiting and information encryption.